2004
DOI: 10.1044/1092-4388(2004/074)
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Speech Perception in Background Noise With Acceptance of Background Noise in Aided and Unaided Conditions

Abstract: Background noise is a significant factor influencing hearing-aid satisfaction and is a major reason for rejection of hearing aids. Attempts have been made by previous researchers to relate the use of hearing aids to speech perception in noise (SPIN), with an expectation of improved speech perception followed by an increased acceptance of hearing aids. Unfortunately, SPIN was not related to hearing-aid use or satisfaction. A new measure of listener reaction to background noise has been proposed. The acceptable … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

16
198
8
4

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 134 publications
(226 citation statements)
references
References 22 publications
16
198
8
4
Order By: Relevance
“…Previous studies concluded that ANL is an individual inherent feature, unaffected by factors like age and degree of hearing loss (Nabelek et al, 2004;Nabelek et al, 2007). In the present study no systematic differences were seen between the ANL on right and left ear.…”
Section: Discussioncontrasting
confidence: 45%
See 4 more Smart Citations
“…Previous studies concluded that ANL is an individual inherent feature, unaffected by factors like age and degree of hearing loss (Nabelek et al, 2004;Nabelek et al, 2007). In the present study no systematic differences were seen between the ANL on right and left ear.…”
Section: Discussioncontrasting
confidence: 45%
“…That would imply that the ANL test has too poor repeatability to predict individual patterns of future hearing aid use. In the already mentioned letter to the editor, Nabelek et al (2007) also reported that in a study (Nabelek et al, 2004), the test-retest difference for individual hearing-impaired listeners was approximately 2 dB. This value was not directly reported in the original paper (Nabelek et al, 2004), but figure 1 in the paper shows testretest differences of about 0-4 dB.…”
Section: Discussionmentioning
confidence: 86%
See 3 more Smart Citations